2015
DOI: 10.5664/jcsm.4698
|View full text |Cite
|
Sign up to set email alerts
|

REM Sleep Behavioral Events and Dreaming

Abstract: Study Objectives: To clarify whether motor behaviors and/ or vocalizations during REM sleep, which do not yet fulfi ll diagnostic criteria for REM sleep behavior disorder (RBD) and were defi ned as REM sleep behavioral events (RBEs), correspond to dream enactments. Methods: 13 subjects (10 patients with Parkinson disease [PD] and 3 healthy controls) originally identifi ed with RBE in a prospective study (DeNoPa cohort) were reinvestigated 2 years later with 2 nights of video-supported polysomnography (vPSG). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Most patients with RBE can recall dream content, and report nonviolent, non-threatening dreams. RBE subjects who at follow-up developed RBD reported more vivid and elaborate dreams [109].…”
Section: Rbd and Other Parasomniasmentioning
confidence: 96%
See 1 more Smart Citation
“…Most patients with RBE can recall dream content, and report nonviolent, non-threatening dreams. RBE subjects who at follow-up developed RBD reported more vivid and elaborate dreams [109].…”
Section: Rbd and Other Parasomniasmentioning
confidence: 96%
“…Interestingly, there is increasing evidence that there may be prodromal stages of RBD, which manifest as minor jerks [91,100,108,109] or REM sleep without atonia [101]. Mollenhauer and co-workers found that even PD patients who did not yet meet the criteria for RBD had more movement during REM sleep [91], and Sixel-Döring and Trenkwalder denominated these seemingly purposeful movements "REM sleep behavioral events" (RBE) and demonstrated that they could represent another prodromal sign of RBD [100,108].…”
Section: Rbd and Other Parasomniasmentioning
confidence: 99%
“…We presented preliminary evidence that these "REM behavioral events" (RBE) not fulfilling RBD defining criteria corresponded to dreaming suggesting that RBE may be a precursor to RBD. 9 We now present the two-year follow-up data to further clarify the role of RBE as a possible very early marker for neurodegeneration and investigate the progression of REM sleep associated behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Nightmares are often distinguished from bad dreams because the nightmares trigger an awakening whereas anxiety dreams are frightening dream experiences remembered only after waking up in the morning ( 123 ). Differently from RBD, during nightmares patients may vocalize or move minimally but complex motor behaviors with enacted dreams of defense against aggressions paralleling dream content usually are lacking ( 131 ). In addition, patients with nightmare disorder exhibit physiological REM atonia during polysomnography ( 85 ).…”
Section: Nightmares and Nightmare Disordermentioning
confidence: 99%